ERAP1 reduces accumulation of aberrant and disulfide-linked forms of HLA-B27 on the cell surface. (June 2016) - Tran, Tri M.; Hong, Sohee; Edwan, Jehad H.; Colbert, Robert A.
Highlights: ERAP1 limits cell surface expression of aberrant disulfide-linked forms of HLA-B27. While limiting expression of aberrant forms of HLA-B27, ERAP1 has no effect on HLA-B51 and -B18 in human monocytic cells. IFN-γ strongly promotes accumulation of aberrant disulfide-linked forms of HLA-B27 even in the presence of ERAP1. Abstract: Objective: Endoplasmic reticulum (ER) aminopeptidase 1 (ERAP1) variants contribute to the risk of ankylosing spondylitis in HLA-B27 positive individuals, implying a disease-related interaction between these gene products. The aim of this study was to determine whether reduced ERAP1 expression would alter the cell surface expression of HLA-B27 and the formation of aberrant disulfide-linked forms that have been implicated in the pathogenesis of spondyloarthritis. Methods: ERAP1 expression was knocked down in monocytic U937 cells expressing HLA-B27 and endogenous HLA class I. The effect of ERAP1 knockdown on the accumulation HLA-B alleles (B18, B51, and B27) was assessed using immunoprecipitation, isoelectric focusing, and immunoblotting, as well as flow cytometry with antibodies specific for different forms of HLA-B27. Cell surface expression of aberrant disulfide-linked HLA-B27 dimers was assessed by immunoprecipitation and electrophoresis on non-reducing polyacrylamide gels. Results: ERAP1 knockdown increased the accumulation of HLA-B27 on the cell surface including disulfide-linked dimers, but had no effect on levels of HLA-B18 or -B51. Antibodies with unique specificity for HLA-B27 confirmed increased cell surface expression of complexes shown previously to contain long peptides. IFN-γ treatment resulted in striking increases in the expression of disulfide-linked HLA-B27 heavy chains, even in cells with normal ERAP1 expression. Conclusions: Our results suggest that normal levels of ERAP1 reduce the accumulation of aberrant and disulfide-linked forms of HLA-B27 in monocytes, and thus help to maintain the integrity of cell surface HLA-B27 complexes.